2019
DOI: 10.1002/anie.201911554
|View full text |Cite
|
Sign up to set email alerts
|

A 3.3 Å‐Resolution Structure of Hyperthermophilic Respiratory Complex III Reveals the Mechanism of Its Thermal Stability

Abstract: Respiratory chain complexes convert energy by coupling electron flow to transmembrane proton translocation. Owing to a lack of atomic structures of cytochrome bc1 complex (Complex III) from thermophilic bacteria, little is known about the adaptations of this macromolecular machine to hyperthermophilic environments. In this study, we purified the cytochrome bc1 complex of Aquifex aeolicus, one of the most extreme thermophilic bacteria known, and determined its structure with and without an inhibitor at 3.3 Å re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 33 publications
(12 reference statements)
2
16
0
Order By: Relevance
“…In our previous study of A. aeolicus complex III, we discovered an extra transmembrane helix of cyt. c 1 and several unique residues important for the thermostability of the complex [20] . Interestingly, we also found that subunit I of AaC c O possesses two additional C‐terminal transmembrane helices, THM13 and TMH14, in comparison with eukaryotic C c Os, or still one additional TMH when comparing with TtC c O, a thermophilic prokaryotic C c O.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…In our previous study of A. aeolicus complex III, we discovered an extra transmembrane helix of cyt. c 1 and several unique residues important for the thermostability of the complex [20] . Interestingly, we also found that subunit I of AaC c O possesses two additional C‐terminal transmembrane helices, THM13 and TMH14, in comparison with eukaryotic C c Os, or still one additional TMH when comparing with TtC c O, a thermophilic prokaryotic C c O.…”
Section: Discussionsupporting
confidence: 50%
“…Based on cryo‐EM 3D classification using RELION [21] (Figure S2), we found two well‐aligned classes of particles existing in the current purified sample. The first class represents the structure of dimeric complex III reported by us before [20] and the second represents the structure of dimeric AaC c O. Our substantial image processing does not suggest the existing of any potential supercomplex in this sample.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…TheA aCcOs ample was enriched by anion exchange chromatography and further purified by size-exclusion chromatography,a nd the fractions showing ad ominant homogenous band around 242 kDa in Blue Native PAGE were used for subsequent cryo-EM experiments (Figure S1). Based on cryo-EM 3D classification using RELION [21] (Figure S2), we found two well-aligned classes of particles existing in the current purified sample.T he first class represents the structure of dimeric complex III reported by us before [20] and the second represents the structure of dimeric AaCcO. Our substantial image processing does not suggest the existing of any potential supercomplex in this sample.A fter in silico purification, the dimeric AaCcOs tructure was determined at af inal resolution of 3. a 3 and from heme a 3 to Cu B are 5.0 and 5.1 ,respectively.…”
Section: Overall Structure Of Aacco Dimermentioning
confidence: 71%